Envenomation by an arachnid (Latrodectus or Steatoda): Case report involving a woman and her female dog - Julián Felipe Porras-Villamil; Mario Javier Olivera; Ángela Catalina Hinestroza-Ruiz; Gabriela Andrea López-Moreno (Case Reports)
Introduction: Accidents involving spiders bites usually cause mild medical reactions that lead to local symptoms and, less commonly, systemic effects. The most medically significant spiders belong to the genera Latrodectus and Loxosceles. This paper presents a posible case of steatodism in a young woman and her pet.